Mischocyttarus (Mischocyttarus) Aripuanaensis. A new social wasp from western-central Brazil, and redescription of Mischocyttarus Lindigi Richards (Hym., Vespidae, Polistinae) - Silveira, Orlando Tobias (Papéis Avulsos de Zoologia, 1997)
Mischocyttarus aripuanaensis, sp.n. is described from Brazil/MT, and aspects of its external morphology are compared to those of species of the subgenera Mischocyttarus s. str., Saussure and Clypeopolybia Brethes. Mischocyttarus lindigi Richards is redescribed. Information on phylogenetic relationships between the above subgenera is presented and discussed